School Rituals and Educational Practice - Vain, Magister Pablo Daniel (Education Policy Analysis Archives, 2002)
This study on school rituals, based on an socio-anthropology view, has arisen from the hypothesis of the anthropologist Roberto Da Matta. This hypothesis supports the theory that rituals are useful, particularly in a complex society, to promote its social identity and develop its character. Da Matta observes that it is as if the ritual domain were a privileged area from whence to enter the cultural kernel of a society, its main ideology, its system of values. This is the reason why we have put forward the proposal that to enquire about rituals at schools can result in a useful contribution to the analysis of this institution in its reproductive dimension or in the construction of a determined social structure. This research was carried out in three schools in the city of Posadas, Misiones, Argentina. In two of them, the research was pursued as a sustained, long-term and ethnographic observation: students, parents, teachers and the managing staff were interviewed. In the third school, just the teachers and the managing staff were interviewed by means of a probing survey; in both cases, strategies, sources and techniques were combined.